THE PATTERN OF SAFETY AND HEALTH WORK TO PREVENT MUSCULOSKELETAL DISORDERS AT WELDING WORKER IN MAHKAMAH STREET MEDAN - Eka Lestari Mahyuni; Kalsum; Makmur Sinaga (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2018)
The welding worker has a potential risk in their work whereas the posture in welding process was notergonomic. The fatique or musculoskeletal disorders happened at the welding worker shown by theirvertebra disorders and some complaint like feel pain in their bone and muscle. The posture like bendingover to the floor or squate position in a long duration would giving the fatique complaint at the last process.The purpose of this research was to implement the pattern of safety and health work as the preventionaction for decrease the musculoskeletal disorders. This is an observasional survey by using the handycam todocumented the posture and use the Participatory Action Research approach. Nordic body mapquestionnaire used to present the mapping of musculoskeletal disorders that happened at the weldingworker. The results showed the pattern of safety and health work could be implement at the welding workersuch as change the posture with welding in standing posture by using the work bench and do the ergonomicrelaxation in 2-3 minutes if the worker feel pain in the part of their body, then do the full ergonomicexercises after the work. The result show that the workers feel pain at their knee, waist, hand, back andshoulder after their work. When they implement the ergonomic relaxation or exercises the musculoskeletaldisorders are decrease in 67 % than before and feel productive to continue their work. In conclusion, theergonomic exercise and relaxation could decrease the musculoskeletal disorders at the welding worker inMahkamah street Medan. Recommended to the host of welding informal industry to arranged their worktime for implement the ergonomic exercise in daily to decrease the musculoskeletal disorders at weldingprocess.